Analysis of variation of stiffness derivative with Mach number and angle of attack for a supersonic flow - Crasta, Asha; Shabana, Aysha; Monis, Renita; Khan, Sher Afghan (International Organization of Scientific Research ( IOSR ), 2016)
In this paper unified supersonic theory is used to derive the expressions of Stiffness derivative of a wedge in Hypersonic flow. This paper demonstrates the effects of pivot position on the stffness derivative with Mach number and incidence angle. From the above discussion it is seen that behaviour of the stiffness derivative is the same for h = 0 to 0.4 and also for h = 0.8, 0.9, and 1.0. Due to the pivot position variations there is a significant variation of Stiffness derivative with Mach number and incidence angle.